P and Ca digestibility is increased in broiler diets supplemented with the high-phytase HIGHPHY wheat. (20th March 2017) - Scholey, D.; Burton, E.; Morgan, N.; Sanni, C.; Madsen, C. K.; Dionisio, G.; Brinch-Pedersen, H.
Abstract : Around 70% of total seed phosphorus is represented by phytate which must be hydrolysed to be bioavailable in non-ruminant diets. The limited endogenous phytase activity in non-ruminant animals make it common practice to add an exogenous phytase source to most poultry and pig feeds. The mature grain phytase activity (MGPA) of cereal seeds provides a route for the seeds themselves to contribute to phytate digestion, but MGPA varies considerably between species and most varieties in current use make negligible contributions. Currently, all phytases used for feed supplementation and transgenic improvement of MGPA are derived from microbial enzymes belonging to the group of histidine acid phosphatases (HAP). Cereals contain HAP phytases, but the bulk of MGPA can be attributed to phytases belonging to a completely different group of phosphatases, the purple acid phosphatases (PAPhy). In recent years, increased MGPAs were achieved in cisgenic barley holding extra copies of barley PAPhy and in the wheat HIGHPHY mutant, where MGPA was increased to ~6200 FTU/kg. In the present study, the effect of replacing 33%, 66% and 100% of a standard wheat with HIGHPHY wheat was compared with a control diet with and without 500 FTU of supplemental phytase. Diets were compared by evaluating broiler performance, ileal Ca and P digestibility and tibia development, using nine replicate pens of four birds per diet over 3 weeks from hatch. There were no differences between treatments in any tibia or bird performance parameters, indicating the control diet did not contain sufficiently low levels of phosphorus to distinguish effect of phytase addition. However, in a comparison of the two wheats, the ileal Ca and P digestibility coefficients for the 100% HIGHPHY wheat diets are 22.9% and 35.6% higher, respectively, than for the control diet, indicating the wheat PAPhy is functional in the broiler digestive tract. Furthermore, 33% HIGHPHY replacement of conventional wheat, significantly improved Ca and P digestibility over the diet-supplemented exogenous phytase, probably due to the higher phytase activity in the HIGHPHY diet (1804 v . 1150 FTU). Full replacement by HIGHPHY gave 14.6% and 22.8% higher ileal digestibility coefficients for Ca and P, respectively, than for feed supplemented with exogenous HAP phytase at 500 FTU. This indicates that in planta wheat PAPhys has promising potential for improving P and mineral digestibility in animal feed.